Identification of Pseudomonas aeruginosa From the Skin Ulcer Disease of Crocodile Lizards (Shinisaurus crocodilurus) and Probiotics as the Control Measure - Xiong, Yi; Wu, Qiong; Qin, Xudong; Yang, Chengsheng; Luo, Shuyi; He, Jiasong; Cheng, Qingzhen; Wu, Zhengjun (Frontiers in Veterinary Science, 2022)
The crocodile lizard (Shinisaurus crocodilurus) is an endangered ancient reptile species. Captive breeding is an important conservation measure for the potential restoration and recovery of their wild populations. However, a skin ulcer disease caused by an unknown pathogen has become a serious threat to captive breeding individuals. In the current study, based on microbial isolation, we identified Pseudomonas aeruginosa as the dominant pathogen in skin ulcer disease. Chinese skinks (Plestiodon chinensis) were used to verify the pathogenicity of P. aeruginosa in skin ulcer disease in vivo. As expected, subcutaneous inoculation of P. aeruginosa induced skin disease in healthy skinks and P. aeruginosa was re-isolated from the induced skin ulcers. Therefore, P. aeruginosa, an opportunistic and ubiquitous pathogen that causes a wide range of infections, appears to be the main pathogen of the skin disease affecting crocodile lizards. In the aquaculture industry, probiotics are widely used in the prevention and control of animal diseases caused by such pathogens. Here, we administered probiotics to the breeding crocodile lizards for 6 months. The three experiment groups treated with different kinds of probiotics showed significance at controlling case incidence. Three of the four groups treated with probiotics showed significant disease prevention (Effective Microorganisms mixed probiotics P = 0.0374; Double-dose Effective Microorganisms, P = 0.0299; Bacillus subtilis, P = 0.0140, T-test), and CFUs in the water of the breeding enclosures were also inhibited after probiotics usage (P < 0.001, T-test). Our study demonstrated the role of Pseudomonas aeruginosa in development of skin ulcer disease of crocodile lizards in a local zoo and offered the probiotic-based method for control measurements, which would be of benefit for the conservation of endangered reptiles.